MARKOV-BASED DEPLOYMENT APPROACH TO IMPROVE WSN COVERAGE - Abd alnasir R. Finjan; Saad T. Hasson (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
A "wireless sensor network (WSN)" represents a gathering of limited number of sensors that are closely deployed in a recognizing area. The efficiency of any WSNs is heavily depending on the coverage delivered by the deployed sensors. In this paper, a developed "deployment approach" is suggested to improve the WSN coverage, connectivity and reliability. This approach is based on the "Markov process". The distances between sensor node and its neighboring sensors are calculated, and then converted to the probabilities that create the transition matrix. Depending on this transition matrix the distance and toward movement for each sensor are estimated in each iteration. The Simulation results were compared with the GSO results. Our results show that this deployment approach can provide high coverage and good reliability.